Midgut volvulus is a rare cause of intestinal obstruction in adults: A case report. (2019) - Ahmadi Amoli, Hadi; Rahimpour, Ehsan; Firoozeh, Negar; Abbaszadeh-Kasbi, Ali; Jazaeri, Seyed Ali
Highlights: Midgut volvulus is usually diagnosed in first weeks of life, or even, in many cases, before birth. Incidence of midgut malrotation among pediatrics is 1 in 500 livebirths. Incidence of adult midgut malrotation is reported between 0.0001% and 0.19%. This is case rare presentation in which a 34 year old man was presented. With diagnosis of midgut volvulus underwent laparotomy. Abstract: Introduction: The incidence of midgut vovulus is rare in adults. However, a significant number of cases were seen in infant and children. Presentation of case: We report a case of a 34-year-old male who presented to the emergency room with persistent periumbilical abdominal pain without any other symptoms. Contrast-enhanced CT showed clearly the typical finding of midgut volvulus like whirlpool sign, corkscrew sign, and the superior mesenteric vein to the left of superior mesenteric artery. The patient was planned for Ladd's procedure and emergency laparotomy performed successfully with an uneventful postoperative recovery. Discussion: Managing midgut volvulus is based on presentation. In symptomatic cases surgery is the treatment, but in asymptomatic cases, treatment is controversial. Conclusion: Although midgut volvulus is rare in adults, it should be considered as an intestinal obstruction.